2019
DOI: 10.2147/ijn.s195375
|View full text |Cite
|
Sign up to set email alerts
|

<p>Improving the anti-keloid outcomes through liposomes loading paclitaxel&ndash;cholesterol complexes</p>

Abstract: Background: Keloids represent benign fibroproliferative tumors which result from elevated expression of inflammation. Paclitaxel (PTX) was an effective chemotherapeutic agent and has been reported to have anti-fibrotic effects, but the strong hydrophobicity brings a challenge for its clinical application. Purpose: The objective of this study was to improve the water solubility of PTX and investigate its anti-keloid effects. Methods: We prepared a PTX-cholesterol-loaded liposomes (PTXL) by thin film evaporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…By using keloid-bearing nude mice model, Wang et al demonstrated PTX had inhibitory effect on keloids growth (63). In vitro, the authors were able to show that the expression of IL-6 and TNF-a, as well as the production of a-SMA and collagen I, by human keloids fibroblast decreased after paclitaxel administration (63). This is consistent with the conclusion drawn on a rabbit ear hypertrophic scar model.…”
Section: Other Medicines Having Anti-scar Functionssupporting
confidence: 61%
See 2 more Smart Citations
“…By using keloid-bearing nude mice model, Wang et al demonstrated PTX had inhibitory effect on keloids growth (63). In vitro, the authors were able to show that the expression of IL-6 and TNF-a, as well as the production of a-SMA and collagen I, by human keloids fibroblast decreased after paclitaxel administration (63). This is consistent with the conclusion drawn on a rabbit ear hypertrophic scar model.…”
Section: Other Medicines Having Anti-scar Functionssupporting
confidence: 61%
“…This anti-inflammatory and anti-fibrosis effect was also observed in animal models of keloid (63) and hypertrophic scar (64). By using keloid-bearing nude mice model, Wang et al demonstrated PTX had inhibitory effect on keloids growth (63). In vitro, the authors were able to show that the expression of IL-6 and TNF-a, as well as the production of a-SMA and collagen I, by human keloids fibroblast decreased after paclitaxel administration (63).…”
Section: Other Medicines Having Anti-scar Functionsmentioning
confidence: 84%
See 1 more Smart Citation
“…In vitro drug release showed a sustained release of PTX from PTXL. Cellular uptake studies showed that PTXL were partially taken up by human keloid fibroblasts (HKFs) through caveolin-mediated endocytosis rather than clathrin [ 140 ]. PTXL inhibited cell proliferation better than PTX when tested at the same concentration range of 0.05–10 µg/mL.…”
Section: Cholesterol-based Compounds For the Treatment Of Dermatolmentioning
confidence: 99%
“…PTXL inhibited the AKT/GSK3β signaling pathway, thus reducing the production of fibrogenic cytokines such as IL-6, TNF-α and TGF-β, which consequently ameliorated fibrosis progress in keloids. The results showed the potential of PTXL in treating keloids [ 140 ].…”
Section: Cholesterol-based Compounds For the Treatment Of Dermatolmentioning
confidence: 99%